Gender composition and the symbolic value of occupations : new evidence of a u-shaped relationship between gender and occupational prestige based on German microdata - Krüger, Sabine [Verfasser]; Ebner, Christian [Verfasser]; Rohrbach-Schmidt, Daniela [Verfasser] (My University, 2022)
"Occupational prestige is an important yet understudied factor in gender labour market inequality. This study examines the relationship between the gender composition of occupations and the prestige of those occupations, and investigates whether men and women differ in their evaluations. A multilevel analysis based on German microdata generated two key findings. First, occupations that are predominantly male or female tend to be rated as more prestigious than mixed-gender occupations when controlling for pay and educational requirements, suggesting a segregation premium in the symbolic valuation of work in Germany. Second, there is no evidence of a gendered in-group bias in Germany; both men and women consider gender-segregated occupations to be more prestigious, with no preference for occupations dominated by their own gender." (Author's abstract ; BIBB-Doku)
Keywords: G 2.3 Wandel von Arbeit & Wirtschaft; P 1.4 Männer; P 1.3 Frauen; 370; 300; Berufsprestige; Geschlechtersegregation; Soziale Ungleichheit; Männerberuf; Frauenberuf; Qualifikationsanforderung; Einkommensunterschied